Application of Index Match Card Method in Islamic Religious Education Subjects at SDN 107826 Pematang Sijonam - Hafmi, Firma; Tanjung, Ellisa Fitri; Nurzannah, Nurzannah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
The ability to read the Quran to elementary school students is still a significant problem in the field of Islamic religious education, especially in SD Negeri No. 107826 Pematang Sijonam (SD Nege telugu No. 107826 Pematang Sijonam). This problem is due to the traditional and outdated applied methods of learning that do not engage students to learn. This study is conducted to see the effectiveness of the Index Card Match (ICM) method in improving students' reading ability in the Quran. A qualitative case study design approach is used. The subjects of the studies were Muslim students in the school. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive approach, which includes data reduction, data presentation, and conclusion drawing. The results obtained show that the ICM method can increase students' motivation to learn and skills in reading the Quran correctly. Moreover, this method also develops an interactive and collaborative process, making the learning environment fun and encouraging students to learn. Nevertheless, implementing ICM faces challenges as teachers need to prepare more to develop materials and guarantee adequate learning time. This paper suggests that the second method, ICM, should be more widely integrated into practice-based learning, even in subjects requiring more conceptual understanding. Moreover, there is a need for intensive training for the teachers to improve their skills in adequately implementing the ICM method. It is also expected that school policies would promote the utilization of this method by providing enough resources and time to ensure maximum impact on the quality of learning